THE EFFECT OF INFLATION, UNEMPLOYMENT, AND POVERTY ON INCOME INEQUALITY IN INDONESIA - Tohap Parulian; Elcy Handayani Pramita; A. Mahendra (RADJA PUBLIKA, 2025)
This research is intended to know the influence of inflation, unemployment and poverty on income inequality in Indonesia. Population in this research is Indonesia and 24 of them were selected to be the samples for this research through purposive sampling technique. Estimates conducted by the multiple regression analysis. The data that were used in this study were secondary data, consisted of Inflation, Unemployment and Poverty on Income Inequality for the year 2000-2023. The results of this research, that Based on the partial test (t test), the Unemployment and Poverty have significant effect on the Income Inequality in Indonesia. Meanwhile the Inflation has not significant effect on the Income Inequality. Based on the simultan test (F test), Inflation, Unemployment and Poverty have a significant effect on the Income Inequality.